Silence and Sounds: An Autoethnography of Searching for Spirituality during Suicide Bereavement in Life and Research - Čepulienė, Austėja Agnietė (Religions, 2022)
In this article, I used autoethnography to describe and analyze my experience of being bereaved by suicide and researching spirituality during suicide bereavement. The culture silenced my grief, and this is congruent with the experiences of my research participants. The religious community, in my case, did not help me and added to my spiritual and psychological pain. The silenced parts of my loss started to make sounds, such as psychological disturbances, but also as unconscious and conscious choices, which led to immersing myself in the research of spirituality during suicide bereavement. Research on the topic goes hand in hand with my search for spirituality during suicide bereavement and reviewing my loss. My story suggests that despite the negative experiences with Catholic priests, spirituality during suicide bereavement can become a vital resource to find meaning for the loss and the pain of grief and can take many different and even unexpected forms.